An assessment of a simple clinical technique to estimate pharyngeal collapsibility in people with obstructive sleep apnea. Issue 10 (8th April 2020) - Osman, Amal M; Tong, Benjamin K; Landry, Shane A; Edwards, Bradley A; Joosten, Simon A; Hamilton, Garun S; Cori, Jennifer M; Jordan, Amy S; Stevens, David; Grunstein, Ronald R; McEvoy, R Doug; Catcheside, Peter G; et al.
Abstract: Study Objectives: Quantification of upper airway collapsibility in obstructive sleep apnea (OSA) could help inform targeted therapy decisions. However, current techniques are clinically impractical. The primary aim of this study was to assess if a simple, novel technique could be implemented as part of a continuous positive airway pressure (CPAP) titration study to assess pharyngeal collapsibility. Methods: A total of 35 participants (15 female) with OSA (mean ± SD apnea–hypopnea index = 35 ± 19 events/h) were studied. Participants first completed a simple clinical intervention during a routine CPAP titration, where CPAP was transiently turned off from the therapeutic pressure for ≤5 breaths/efforts on ≥5 occasions during stable non-rapid eye movement (non-REM) sleep for quantitative assessment of airflow responses (%peak inspiratory flow [PIF] from preceding 5 breaths). Participants then underwent an overnight physiology study to determine the pharyngeal critical closing pressure (Pcrit) and repeat transient drops to zero CPAP to assess airflow response reproducibility. Results: Mean PIF of breaths 3–5 during zero CPAP on the simple clinical intervention versus the physiology night were similar (34 ± 29% vs. 28 ± 30% on therapeutic CPAP, p = 0.2; range 0%–90% vs. 0%–95%). Pcrit was −1.0 ± 2.5 cmH2 O (range −6 to 5 cmH2 O). Mean PIF during zero CPAP on the simple clinical intervention and the physiology night correlated with Pcrit ( r = −0.7 and −0.9, respectively, p < 0.0001). Receiver operating characteristic curve analysis indicated significant diagnostic utility for the simple intervention to predict Pcrit < −2 and < 0 cmH2 O (AUC = 0.81 and 0.92), respectively. Conclusions: A simple CPAP intervention can successfully discriminate between patients with and without mild to moderately collapsible pharyngeal airways. This scalable approach may help select individuals most likely to respond to non-CPAP therapies.